APC‐targeted proinsulin expression inactivates insulin‐specific memory CD8+ T cells in NOD mice. Issue 9 (11th July 2017) - Reeves, Peta LS; Rudraraju, Rajeev; Liu, Xiao; Wong, F Susan; Hamilton‐Williams, Emma E; Steptoe, Raymond J
Abstract : Type 1 diabetes (T1D) results from T‐cell‐mediated autoimmune destruction of pancreatic β cells. Effector T‐cell responses emerge early in disease development and expand as disease progresses. Following β‐cell destruction, a long‐lived T‐cell memory is generated that represents a barrier to islet transplantation and other cellular insulin‐replacement therapies. Development of effective immunotherapies that control or ablate β‐cell destructive effector and memory T‐cell responses has the potential to prevent disease progression and recurrence. Targeting antigen expression to antigen‐presenting cells inactivates cognate CD8 + effector and memory T‐cell responses and has therapeutic potential. Here we investigated this in the context of insulin‐specific responses in the non‐obese diabetic mouse where genetic immune tolerance defects could impact on therapeutic tolerance induction. Insulin‐specific CD8 + memory T cells transferred to mice expressing proinsulin in antigen‐presenting cells proliferated in response to transgenically expressed proinsulin and the majority were rapidly deleted. A small proportion of transferred insulin‐specific Tmem remained undeleted and these were antigen‐unresponsive, exhibited reduced T cell receptor (TCR) expression and H‐2K d /insB15‐23 tetramer binding and expressed co‐inhibitory molecules. Expression of proinsulin in antigen‐presenting cells also abolished the diabetogenic capacity of CD8 + effector T cells. Therefore, destructive insulin‐specific CD8 + T cells are effectively inactivated by enforced proinsulin expression despite tolerance defects that exist in diabetes‐prone NOD mice. These findings have important implications in developing immunotherapeutic approaches to T1D and other T‐cell‐mediated autoimmune diseases.